Quercetin in Drug Carriers: Polymer Composite, Physical Characteristics, and In vitro Study - Kurniawan, Muhammad Fariez; Setyawan, Dwi; Hariyadi, Dewi Melani (Science and Technology Indonesia, 2024)
Quercetin is a highly prevalent flavonoid commonly found in a wide variety of fruits and vegetables. This compound has various biological actions, indicating great potential in preventing diseases and promoting health but the disadvantages include low solubility and instability. The disadvantages can be overcome by using a polymer composite in the form of microspheres in the formulation. Therefore, this study aimed to review various uses of polymers in delivering quercetin compounds. The results showed that various polymers in microspheres have been formulated with quercetin to minimize the weaknesses. The delivery systems developed and reported from several related studies include microencapsulation, microcapsules, microparticles, microspheres, solid lipid microparticles (SLM), and nanoparticles. Polymers including Gelatine, Maltodextrin and Inulin, Carnauba wax, Poly (lactic-co-glycolic acid (PLGA), Gyceryl behenate, Pectin, Nano-hydroxyapatite, Polycaprolactone, Starch, Chitosan, Eudragit S 100, Sodium Alginate, Ethyl cellulose, and Alumina efficiently improved the properties of quercetin, enabling the utilization as a controlled drug delivery agent. Therefore, developing a quercetin delivery system using composite polymers presents both an opportunity and a challenge for future applications.